How Effective are Macroprudential Policies in China? - Wang, Bin (IMF Working Papers; Working Paper ;, 2013)
This paper investigates macroprudential policies and their role in containing systemic risk in China. It shows that China faces systemic risk in both the time (procyclicality) and cross-sectional (contagion) dimensions. The former is reflected as credit and asset price risks, while the latter is reflected as the links between the banking sector and informal financing and local government financing platforms. Empirical analysis based on 171 banks shows that some macroprudential policy tools (e.g., the reserve requirement ratio and house-related policies) are useful, but they cannot guarantee protection against systemic risk in the current economic and financial environment. Nevertheless, better-targeted macroprudential policies have greater potential to contain systemic risk pertaining to the different sizes of the banks and their location in regions with different levels of economic development. Complementing macroprudential policies with further reforms, including further commercialization of large banks, would help improve the effectiveness of those policies in containing systemic risk in China.